ROTATING BLADE MECHANISM FOR CLEANING CYLINDRICAL SENSORS (2023)
The subject disclosure relates to features that facilitate the automatic cleaning of optical sensors and in particular Light Detection and Ranging (LiDAR) sensors used in autonomous vehicle deployments. In some aspects, the disclosed technology includes a sensor cleaning apparatus having a housing, wherein the housing is configured to be rotatably coupled to an optical sensor, a wiper blade coupled to the housing, wherein the wiper blade is disposed at a downward angle relative to a top-surface of the optical sensor, and one or more nozzles disposed within the wiper blade, wherein the nozzles are configured to apply compressed gas to a surface of the optical sensor.